Volume 1: Turbomachinery 1994
DOI: 10.1115/94-gt-106
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Radial Inflow on Rotor-Stator Cavity Pressure Distributions

Abstract: Rig tests and computational fluid dynamic (CFD) modelling have been used to improve the understanding of the effect% of component geometry and air bleed flows on the pressure and velocity variations in the rotor-stator cavity found typically behind the impeller of a gas turbine engine centrifugal compressor.Ranges of axial gap ratio and bleed throughflow typical of those found in current gas turbine engine design have been investigated with close attention to radial inflow (centripetal) bleeds with and without… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…This choice was based on various considerations, such as similarity in geometric configuration and flow conditions. The experimental data for the validation test come from Hart and Turner [12]. Figure 4 shows a schematic diagram of the fully shrouded rotor-stator system consisting of a rotor of 400 mm diameter (b=400 mm), spinning at up to 4400 r/min and separated from a shrouded stator by an axial air gap which can be varied from 2-23 mm in width.…”
Section: Validation Of the Computational Modelmentioning
confidence: 99%
“…This choice was based on various considerations, such as similarity in geometric configuration and flow conditions. The experimental data for the validation test come from Hart and Turner [12]. Figure 4 shows a schematic diagram of the fully shrouded rotor-stator system consisting of a rotor of 400 mm diameter (b=400 mm), spinning at up to 4400 r/min and separated from a shrouded stator by an axial air gap which can be varied from 2-23 mm in width.…”
Section: Validation Of the Computational Modelmentioning
confidence: 99%
“…A substantial amount of work has been performed by numerous researchers on the flow of fluid close to rotating discs. Hart and Turner (1994) contains a basic chronological review of some of this work and its relevance to rotor-stator cavity velocity and pressure variations.…”
Section: Theory and Review Of Previous Workmentioning
confidence: 99%
“…In order to promote confidence in the use of this CFD code for the assessment of impeller rear face rotor-stator cavity geometries and through flows, CFD models were produced to validate the code at most of the geometry and flow conditions tested on the experimental rig. This validation process was reported in Hart and Turner (1994).…”
Section: Computational Fluid Dynamics (Cfd)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is found that the value of β 0 has a significant influence on the distribution of the swirl ratio β in the central core region. Hart and Turner [9,10] used numerical and experimental methods to obtain the pressure and swirl ratio in the impeller rear cavities with different geometries and air bleed flow. The aim of their researches was to obtain a series of curves that can help predict velocity and pressure distribution quickly and accurately without the need for costly CFD work or rig testing during the initial engine design phase.…”
Section: Introductionmentioning
confidence: 99%